Kandungan Fitokimia, Total Fenol, dan Total Flavonoid Ekstrak Buah Harendong (Melastoma affine D. Don) - Novilia Eka Syafitri; Maria Bintang; Syamsul Falah (IPB University, 2014)
Melastoma affine plant has effect on health such as curing wound and toothache, also as an antimalarial drug. The fruit of this plant is purple and probably contain secondary metabolite compounds such as phenols and flavonoids. The total amount of both compounds may be different in unripe and ripe fruit. The aims of this research were to analyze secondary metabolite compounds and determine total phenol and total flavonoid of Melastoma affine fruit extract. The samples used in this study were unripe and ripe Melastoma affine fruits. Both of samples were extracted by three different solvents (water, 70% ethanol, and 96% ethanol) and obtained 6 extracts. Based on phytochemical test, each extract from unripe and ripe Melastoma affine fruit contained alkaloid, triterpenoid, flavonoid, phenol, and tanin. The extract with highest total phenols was 70% ethanolic extract from unripe fruit (189.56 mg/g GAE), while the extract with highest total flavonoids was 96% ethanolic extract from unripe fruit (225.50 mg/g CE). Based on this result, we conclude that unripe fruit of Melastoma affine has more total phenols and total flavonoids than ripe fruit.